2018
DOI: 10.1042/bsr20180576
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA PVT1, a molecular sponge for miR-149, contributes aberrant metabolic dysfunction and inflammation in IL-1β-simulated osteoarthritic chondrocytes

Abstract: Osteoarthritis (OA), a common form of degenerative joint disease, is typified by inflammatory response and the loss of cartilage matrix. Long non-coding RNAs (lncRNAs) are emerging as a new player in gene regulation and exert critical roles in diverse physiologic and pathogenic processes including OA. The lncRNA plasmacytoma variant translocation 1 (PVT1) has been implicated in cancer, diabetes and septic acute kidney injury. Recent research confirmed the elevation of PVT1 in patients with OA. However, its rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…In line with our findings, the anti-apoptotic protein Bcl2 was enhanced, whereas the pro-apoptotic gene Bax was suppressed by silencing of signal transducer and activator of transcription 3 through delivering small interfering RNA in RA-FLSs [28]. Interestingly, PVT1 could directly bind to miR-149 as an endogenous sponge RNA and miR-149 suppression reversed the protective roles of PVT1 knockdown in attenuating IL-1β-evoked inflammation in osteoarthritic chondrocytes [29]. In addition, silencing of PVT1 promoted cell proliferation, yet suppressed inflammation in C28/I2 cells stimulated by IL-1β, which was counteracted by the deficiency of its target miR-27b-3p [30].…”
Section: Discussionsupporting
confidence: 88%
“…In line with our findings, the anti-apoptotic protein Bcl2 was enhanced, whereas the pro-apoptotic gene Bax was suppressed by silencing of signal transducer and activator of transcription 3 through delivering small interfering RNA in RA-FLSs [28]. Interestingly, PVT1 could directly bind to miR-149 as an endogenous sponge RNA and miR-149 suppression reversed the protective roles of PVT1 knockdown in attenuating IL-1β-evoked inflammation in osteoarthritic chondrocytes [29]. In addition, silencing of PVT1 promoted cell proliferation, yet suppressed inflammation in C28/I2 cells stimulated by IL-1β, which was counteracted by the deficiency of its target miR-27b-3p [30].…”
Section: Discussionsupporting
confidence: 88%
“…li et al (13) revealed that PVT1 enhancement facilitates cell apoptosis in chondrocytes in osteoarthritis. a previous study stated that increased PVT1 expression expedites inflammation and aberrant metabolic dysfunction in il-β-induced chondrocytes (38). PVT1 is associated with the development of hyperglycemia-induced collagen degradation in chondrocytes (36).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies suggest that PVT1 can be used as a sponge for mirnas to participate in the development of osteoarthritis (13,38,39). mir-93-5p-containing exosomes attenuated the myocardial injury caused by acute myocardial damage (40).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study also found that silencing LINC01534 significantly reduced the contents of PGE2, NO, IL-6, IL-8, and TNF-α in the chondrocyte supernatant induced by IL-1β, while miR-140-5p inhibitor showed the opposite effect. Zhao et al found that lncRNA PVT1 inhibited the expression of aggrecan and collagen II in IL-1β-induced OA chondrocytes by targeting miR-149, up-regulated the secretions of MMPs, TNF-α, IL-8, IL-6, NO, and PGE2, and ultimately aggravated chondrocyte catabolism and inflammation (36).…”
Section: Discussionmentioning
confidence: 99%